2022
DOI: 10.3390/app12020540
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT versus Bone Marrow Biopsy for Diagnosis of Bone Marrow Involvement in Non-Hodgkin Lymphoma: A Systematic Review

Abstract: The management of non-Hodgkin lymphoma (NHL) patients requires the identification of bone marrow involvement (BMI) using a bone marrow biopsy (BMB), as recommended by international guidelines. Multiple studies have shown that [18F]FDG positron emission tomography, combined with computed tomography (PET/CT), may provide important information and may detect BMI, but there is still an ongoing debate as to whether it is sensitive enough for NHL patients in order to replace or be used as a complimentary method to B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 63 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…In a study conducted by Teagle et al [12], it was concluded that FDG PET/CT has 100% sensitivity and specificity for detecting bone marrow involvement in DLBCL, keeping bone marrow biopsy as the reference standard. In a recent systematic review by Almaimani et al [10], including 41 studies, the total number of patients with DLBCL was 2336; among the included studies with patients' data of DLBCL for PET/CT, the sensitivity, specificity, PPV, and NPV were 77.40%, 91.65%, 63.60%, and 97.00%, respectively, and the sensitivity of BMB in finding out BMI was 47.00%, specificity was 100%, PPV was 100%, and NPV was 80.00%. In another recent study conducted by Xiao-Xue and coworkers [18], it was found that the sensitivity, specificity, and accuracy of PET/CT to detect BMI in aggressive B cell lymphoma (DLBCL and Burkitt lymphoma) were 80.0%, 90.0%, and 88.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study conducted by Teagle et al [12], it was concluded that FDG PET/CT has 100% sensitivity and specificity for detecting bone marrow involvement in DLBCL, keeping bone marrow biopsy as the reference standard. In a recent systematic review by Almaimani et al [10], including 41 studies, the total number of patients with DLBCL was 2336; among the included studies with patients' data of DLBCL for PET/CT, the sensitivity, specificity, PPV, and NPV were 77.40%, 91.65%, 63.60%, and 97.00%, respectively, and the sensitivity of BMB in finding out BMI was 47.00%, specificity was 100%, PPV was 100%, and NPV was 80.00%. In another recent study conducted by Xiao-Xue and coworkers [18], it was found that the sensitivity, specificity, and accuracy of PET/CT to detect BMI in aggressive B cell lymphoma (DLBCL and Burkitt lymphoma) were 80.0%, 90.0%, and 88.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common methods used for the detection of BMI by the underlying lymphoma is bone marrow biopsy (BMB) [10]. Although BMB is considered a gold standard and a safe procedure for the evaluation of BMI, it has certain limitations and risks [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-Hodgkin lymphoma (NHL) constitutes approximately 4% of annual cancer diagnoses. It ranks as the sixth most common cause of cancer and accounts for almost 6% of malignancy-related mortality in Europe and the United States ( 1 3 ). Within the spectrum of NHL, diffuse large B cell lymphoma (DLBCL) emerges as the most prevalent subtype, accounting for 30 – 40% of aggressive NHL cases in adults worldwide ( 3 7 ).…”
Section: Introductionmentioning
confidence: 99%